2021
DOI: 10.1101/2021.06.17.21258764
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduction in left frontal alpha oscillations by transcranial alternating current stimulation in major depressive disorder is context-dependent in a randomized-clinical trial

Abstract: Background: Left frontal alpha oscillations are associated with decreased approach motivation and have been proposed as a target for non-invasive brain stimulation for the treatment of depression and anhedonia. Indeed, transcranial alternating current stimulation (tACS) at the alpha frequency reduced left frontal alpha power and was associated with a higher response rate than placebo stimulation in patients with major depressive disorder (MDD) in a recent double-blind placebo controlled clinical trial. Methods… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
8
1
Order By: Relevance
“…Critically, the analysis of brain activity as a function of menstrual phase prior to stimulation provides an understanding of the neural activity that was impacted by stimulation. In our previous study on major depressive disorder, we found that patients within a major depressive episode showed elevated left frontal alpha oscillations while processing positive valence images and that this pathologically elevated left frontal alpha activity was reduced by alpha-tACS (Riddle et al, 2022). By contrast, in this case series, patients with PMDD showed decreased alpha activity over the frontal-midline during the late luteal phase and this activity was increased by alpha-tACS.…”
Section: J O U R N a L P R E -P R O O Fcontrasting
confidence: 57%
“…Critically, the analysis of brain activity as a function of menstrual phase prior to stimulation provides an understanding of the neural activity that was impacted by stimulation. In our previous study on major depressive disorder, we found that patients within a major depressive episode showed elevated left frontal alpha oscillations while processing positive valence images and that this pathologically elevated left frontal alpha activity was reduced by alpha-tACS (Riddle et al, 2022). By contrast, in this case series, patients with PMDD showed decreased alpha activity over the frontal-midline during the late luteal phase and this activity was increased by alpha-tACS.…”
Section: J O U R N a L P R E -P R O O Fcontrasting
confidence: 57%
“…Marginalized across channel, the α and β * oscillatory powers demonstrate significant, consistent deviations from zero (Figure 3c) indicating that different patterns of EEG changes are evoked across the scalp. While DBS has historically focused on β oscillations[10, 35, 36], including in our own group’s intraoperative observations [13, 37], α has been shown to be modulated by neuromodulation [8, 38] and to be linked to depressed mood [39, 40, 41, 42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…The left dlPFC plays a key role in positive emotions and it is sometimes affected by disorders that lead to increased alpha oscillations in EEG. According to the study, increased left frontal alpha oscillations are associated with MDD, tACS can reduce these oscillations [24].…”
Section: Transcranial Direct Current Stimulation and Transcranial Alt...mentioning
confidence: 91%